2011
DOI: 10.1161/strokeaha.111.613653
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intravenous Tissue-Type Plasminogen Activator in Central Retinal Artery Occlusion

Abstract: Background and Purpose-Central retinal artery occlusion is caused by a platelet-fibrin thrombus or embolic occlusion and is a stroke of the eye. Observational studies suggest that thrombolytics may restore ocular perfusion and visual function. We hypothesized that intravenous tissue-type plasminogen activator (tPA) administered within 24 hours of symptom onset might restore ocular perfusion and visual function. Methods-A placebo-controlled, randomized trial of intravenous tPA versus intravenous saline was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
75
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 24 publications
3
75
0
11
Order By: Relevance
“…Most studies included a small number of subjects, were conducted using a retrospective study design, and reported limited effectiveness of the tested treatments. As we also found, some studies found correlations between shorter time to treatment and favorable visual outcomes, 6,[8][9][10]16 whereas others found no significant effects of time to treatment on visual outcomes. 13,14 Restoration of possible blood flow or vasodilation after treatments was examined in several studies.…”
Section: Discussionsupporting
confidence: 79%
“…Most studies included a small number of subjects, were conducted using a retrospective study design, and reported limited effectiveness of the tested treatments. As we also found, some studies found correlations between shorter time to treatment and favorable visual outcomes, 6,[8][9][10]16 whereas others found no significant effects of time to treatment on visual outcomes. 13,14 Restoration of possible blood flow or vasodilation after treatments was examined in several studies.…”
Section: Discussionsupporting
confidence: 79%
“…4 A small randomized trial (n=16) on intravenous tissue-type plasminogen activator found improved visual acuity in 25% of patients, versus none after placebo. 3 For the first time, we correlated treatment effects with the occurrence of a spot sign. We found relevant treatment effects only in spot sign-negative CRAO.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating intra-arterial or intravenous thrombolysis have yielded inconsistent results. [2][3][4] Ocular color-coded duplex sonography (OCCS) allows direct examination of the central retinal artery. Only few studies report on its value.…”
mentioning
confidence: 99%
“…This is the only gold standard trial to be undertaken to date but, in the event, safety concerns among patients undergoing LIF led to its abandonment at a stage when there was no significant difference in functional outcomes between the 2 study arms (Schumacher et al, 2010). Nevertheless, further trials are planned or recommended, not least to determine the role of fibrinolytic intervention within a narrower time-window from CRAO onset (Aldrich et al, 2008;Biousse, 2008;Atkins et al, 2009;Schumacher et al, 2010;Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%